Application of Theory of Constraint Supply Chain Replenishment System in Fast Moving Consumer Goods Company - Taufik Roni Sahroni; Margaretha Margaretha; Dyah Budiastuti (International Journal of Supply Chain Management, 2017)
Todays market competitiveness has reached its peak since the rapid growth of industrial and technology development. The market dominance aims to fulfill the consumer supply and demand, by giving excellent service, such as stabilizing the finished goods inventory level in the right time and quantity.XYZ is one of the Fast Moving Consumer Goods (FMCG) Company which has several problems in supplying their product to market. Actual market condition and demand become the main factor why the company is unable fulfilling the right product to its consumer, despite the Production Planning and Inventory Control (PPIC) segment has made the right production target based on the Purchase Order and Selling Target from Distributors Company. Thus, further development by combining supply chain management system with several theory of constraints is required to manage the material inventory and finished goods, which meet the consumer needs such as integrated master production schedule, market demand condition, finished goods inventory, and material replenishment by suppliers.